The Relationship between Academic Self-Efficacy and Cognitive Flexibility: Physical Education and Sports Teacher Candidates - Pepe, Şirin (2021)
The aim of this study is to examine the relationship between academic self-efficacy and cognitive flexibility levels of physical education and sports teacher candidates. The universe of the study consisted of 480 teacher candidates studying in the physical education and sports teaching departments of the sports sciences faculties within Selçuk, Erciyes, Süleyman Demirel and Mehmet Akif Ersoy Universities, and the sample group consisted of 192 volunteers from the specified population. Participants in the study were asked to fill in a personal information form, academic self-efficacy and cognitive flexibility scales. IBM SPSS 22.0 (Statistical Package for the Social Sciences) statistical package program was used to analyze the data. Arithmetic means and standard deviations of the scores of the volunteers from the scales were presented as X±Sd. Pearson Product Moment Correlation Analysis was applied to reveal the relationship of the data obtained from the scales. The value of p<0,05 was considered significant. As a result, it was determined that the academic self-efficacy and cognitive flexibility levels of physical education and sports teacher candidates were above average. A moderate positive correlation was found between academic self-efficacy and alternatives and control subtitles of cognitive flexibility and total of cognitive flexibility. It is thought that this situation is due to the ability of physical education and sports teacher candidates to transfer their experiences in sports life to their education life.